Strategy-proofness and efficiency for non-quasi-linear common-tiered-object preferences: Characterization of minimum price rule - Yu Zhou; Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2016)
We consider the allocation problem of assigning heterogenous objects to a group of agents and determining how much they should pay. Each agent receives at most one object. Agents have non-quasi-linear preferences over bundles, each consisting of an object and a payment. Especially, we focus on the cases: (i) objects are linearly ranked, and as long as objects are equally priced, agents commonly prefer a higher ranked object to a lower ranked one, and (ii) objects are partitioned into several tiers, and as long as objects are equally priced, agents commonly prefer an object in the higher tier to an object in the lower tier. The minimum price rule assigns a minimum price (Walrasian) equilibrium to each preference profile. We establish: (i) on a common-object-ranking domain, the minimum price rule is the only rule satisfying efficiency, strategy-proofness, individual rationality and no subsidy, and (ii) on a common-tiered-object domain, the minimum price rule is the only rule satisfying these four axioms.
Keywords: D44; D61; D71; D82; 330; strategy-proofness; efficiency; non-quasi-linearity; minimum price rule; common-object-ranking domain; common-tiered-object domain